Speaking of Culture - Weil, Nolan; Open Textbook Library (Open Textbook Library, 2017)
"Speaking of Culture" is a collection of instructor-authored background readings intended to accompany other activities, discussions, experiences, projects, and readings for IELI 2470 - Cross-Cultural Perspectives, a course offered by faculty in the Intensive English Language Institute at Utah State University. Its main purpose is to define culture and other concepts often associated with it.
Chapter 1: What is Culture? -- Chapter 2: The Human Family -- Chapter 3: Origins and Early Developments of Culture -- Chapter 4: Material Culture -- Chapter 5: Culture as Thought and Action -- Chapter 6: Beliefs, Values, and Cultural Universals -- Chapter 7: Group Membership and Identity -- Chapter 8: Roots of American National Culture
In English.
Description based on print resource
Keywords: Sociology -- Textbooks